2018
DOI: 10.2166/wst.2018.485
|View full text |Cite
|
Sign up to set email alerts
|

Final products and kinetics of biochemical and chemical sulfide oxidation under microaerobic conditions

Abstract: Hydrogen sulfide is a toxic and usually undesirable by-product of the anaerobic treatment of sulfate-containing wastewater. It can be removed through microaeration, a simple and cost-effective method involving the application of oxygen-limiting conditions (i.e., dissolved oxygen below 0.1 mg L−1). However, the exact transformation pathways of sulfide under microaerobic conditions are still unclear. In this paper, batch experiments were performed to study biochemical and chemical sulfide oxidation under microae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…On the OFR analysis, there can be observed that the fermentation of sour cabbage hydrogen production is more sensitive than methane production. This showed that in the case of high VSS [75] there were some ranges improving methane production yield that agreed with comparisons of Nguyen et al [25] (fixing metabolism in the anaerobic digestion of lignocellulose), and Krayzelova et al [76] (reduction of hydrogen sulfide). It can be discerned that after the 11 th day (265 hours) a significant growth of hydrogen production was observed -see Figure 4, due to pH decrease (to 5.1).…”
Section: Total Hydrogen Production Vs Total Hydrogen Sulphite Production and General Discussionsupporting
confidence: 88%
“…On the OFR analysis, there can be observed that the fermentation of sour cabbage hydrogen production is more sensitive than methane production. This showed that in the case of high VSS [75] there were some ranges improving methane production yield that agreed with comparisons of Nguyen et al [25] (fixing metabolism in the anaerobic digestion of lignocellulose), and Krayzelova et al [76] (reduction of hydrogen sulfide). It can be discerned that after the 11 th day (265 hours) a significant growth of hydrogen production was observed -see Figure 4, due to pH decrease (to 5.1).…”
Section: Total Hydrogen Production Vs Total Hydrogen Sulphite Production and General Discussionsupporting
confidence: 88%
“…Sulfur is expected to be the primary end product of biological sulfide-oxidation for oxygen concentrations below 0.1 mg/L, with partial oxidation to thiosulfate. With higher oxygen availability, sulfate is expected to be the predominant end-product (Pokorna-Krayzelova et al, 2018). The amount of dissolved oxygen can be associated with the aeration rate and the use in the biochemical reaction; hence, optimizing aeration is crucial to prevent low or incomplete sulfideoxidation (Pokorna & Zabranska, 2015).…”
Section: Integrated Anaerobic/aerobic Biological System (Iaab)mentioning
confidence: 99%
“…In Pokorna-Krayzelova et al (2017b), ADM1 was extended by sulfur reactions (sulfate reduction and sulfide oxidation) in anaerobic/microaerobic fermenters. The resulting model ADM1-S/O was later extended by chemical oxidation of hydrogen sulfide (Pokorna-Krayzelova et al, 2018b).…”
Section: Model-based Optimizationmentioning
confidence: 99%